Validation of the Lifetime Incidence of Traumatic Events (LITE-S/P) Questionnaires in Children and Adolescents in Slovenia - Uršič, Katarina; Bucik, Valentin; Klemenčič, Simona; Bratina, Nataša; Battelino, Tadej; Dovč, Klemen; Drobnič Radobuljac, Maja (Frontiers in Psychiatry, 2021)
Introduction A traumatic event is an extremely threatening and frightening experience in an individual’s life. Children who are exposed to traumatic events are twice as likely to develop a mental disorder. Screening can provide insight into the traumatic experience of children, identifying those eligible for further evaluation and support. With this aim, we evaluated the psychometric properties of the Lifetime Incidence of Traumatic Events questionnaire (LITE) in Slovene by calculating retest reliabilty, construct validity (cross-informant agreement) and external validity, where we calculated the correlation of the number of differenet traumatic events with psychopathological symptoms. Methods 280 child-parent pairs (children aged 11.3 ± 2.2 years) from various Slovenian primary schools participated in the study. They were divided into two groups: 180 healthy primary school students and 100 children with Type 1 Diabetes (our study was a part of a larger study The Influence of Psychobiological Adversity on Children and Adolescents with Type 1 Diabetes Study). Two versions of the LITE questionnaire were used. Children completed the child report (LITE-S) and parents the parent report (LITE-P) version. After four weeks, 117 children and 114 parents filled out the LITEs again. External validity was assessed using the Youth Self Report and Child Behaviour Checklist syndrome-oriented scales. Results Retest reliability for individual scales was r = 0.469 - 0.639 ( = 0.443 - 0.636; p < 0.001), but higher for individual items (κ = 0.263 - 0.821; p < 0.001). Correlations between reports from parents and children were r = 0.313 - 0.345 ( = 0.317-0.348; p < 0.001). The number of different events experienced by children correlated significantly with the measured depressive – anxiety and posttraumatic stress disorder symptoms. Conclusions Based on our results, the LITE-S and LITE-P “All events” scale have acceptable psychometric properties for use in research and in clinical practice screening. We recommend looking at single items, taking into consideration the responses from both the child and the parent for more precise information. To improve the precision of the psychodiagnostic capacity of the questionnaire, further research on various populations should be performed.